MANAGEMENT OF CROUP IN CHILDREN: A CASE REPORT - Wenly Susanto; Novia Bella Rianto; Dewa Agung Ayu Sridharaswari (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background Croup is a viral respiratory disease in children that attacks the larynx and trachea causes obstruction or blockage of the upper respiratory tract which, if severe, can be life-threatening.  Diagnosis of respiratory tract infection in children requires keen clinical vigilance to understand the risk of airway obstruction and the possible need for prompt intervention. Clinical symptoms in croup usually fever, runny nose, painful swallowing, and mild cough. This condition can develop into a loud, hoarse and harsh cough. Recognition of signs and symptoms is very important to prevent morbidity and mortality. Objective To describe diagnosis and management of croup in children. Case Description  A 3-year-old boy, came to the emergency room with complaints of sudden shortness of breath this morning accompanied by fever and a barking cough. These complaints had been felt for 3 days before going to the hospital, but they can reduce on their own and according to the parents there were no danger signs for complaints in their children. Conclusion  Croup is a self-limited disease, but sometimes it tends to be severe and even fatal. Prompt and appropriate management can prevent or reduce the risk of croup morbidity and mortality in children .